Metaphysics in a Review of "Karl Popper's Philosophy of Science" (Rationality Without Foundations) by Stefano Gattei - Binar Kurnia Prahani; Sayidah Mahtari; Suyidno; Joko Siswanto; Wahyu Hari Kristiyanto (IJORER : International Journal of Recent Educational Research, 2020)
This article is the result of a book review of a work by Stefano Gattei. The starting point of Popper's view is that "almost every phase of our scientific development is under metaphysical rule, that is, ideas that are tested, ideas which determine not only what problems we need to explain, but also what kinds of answers we will consider to be one that is important or satisfactory or accepted, and as a remedy, or guarantee, of a previous answer". Popper's indeterminism is important because Popper's custom begins by considering an intuitive Laplacian view of determinism: "the world is like a motion picture film: or a projected image. Parts of the film have proved to be the past. And unproven people are the past. front". Popper has always been claimed to be a metaphysical realist: to him, to be a realist means to think, in covenant with common sense, that the world of his existence is independent of human beings. It means, "my existence will end without the world coming to an end too". As well as other metaphysical positions, realism is a non-testable conjecture: "realism is neither proven nor disproved".